Edukasi Pemanfaatan Terapi Komplementer Untuk Mengurangi Kejadian Emesis Gravidarum Pada Kehamilan Trimester Pertama - Arini, Ketut Novia (STIKES Advaita Medika Tabanan, 2023)
In the philosophy of maternity care, it is believed that the changes that occur in women during pregnancy are physiological. One of the complaints that often appears in early pregnancy (generally in the first months of pregnancy until the end of the first trimester) is emesis gravidarum. Nausea and vomiting are normal symptoms and are often experienced in the first trimester of pregnancy. The development of complementary therapies has recently been in spotlight in various countries. Complementary or alternative medicine is an important part of health services. Some research results say that the use of aromatherapy can help to reduce complaints of nausea and vomiting during pregnancy. There are various kinds of aromatherapy that can be used, namely peppermint, lemon, lavender ginger aromatherapy. This activity was carried out for 40 days, starting with coordinating with village heads and primary health care, outreach to the implementation of education. This education involves six students and two supervisors with the target of education being 50 people. The provision of education significantly increases the knowledge of pregnant women on the use of complementary therapies to treat emesis gravidarum.